Role of Algal-derived Bioactive Compounds in Human Health - Tripathi G.; Dubey P.; Ahmad S.; Farooqui A.; Mishra V. (My University, 2025)
Algae is emerging as a bioresource with high biological potential. Various algal strains have been used in traditional medicines and human diets worldwide. They are a rich source of bioactive compounds like ascorbic acid, riboflavin, pantothenate, biotin, folic acid, nicotinic acid, phycocyanins, gamma-linolenic acid (GLA), adrenic acid (ARA), docosahexaenoic acid (DHA), eicosapentaenoic acid (EPA), etc. Beta-carotene, astaxanthin, and phycobiliproteins are different classes of pigments that are found in algae. They possess antioxidant, anti-inflammatory and anticancer properties. The sulfur-coated polysaccharides in algae have been used as an anticancer, antibacterial, and antiviral agent. Scientists have exploited algal-derived bioactive compounds for developing lead molecules against several diseases. Due to the surge in research on bioactive molecules from algae, industries have started showing interest in patenting for the large-scale production of bioactive compounds having applications in sectors like pharmaceuticals, food, and beverage. In the food industry, algae are used as a thickening, gelling, and stabilizing agent. Due to their gelling and thickening characteristics, the most valuable algae products are macroalgal polysaccharides such as agar, alginates, and carrageenan. The high protein, lipid, and nutrient content in microalgae makes it a superfood for aquaculture. The present review aims at describing various non-energy-based applications of algae in pharmaceuticals, food and beverage, cosmetics, and nutraceuticals. This review attempts to analyze information on algal-derived drugs that have shown better potential and reached clinical trials. © 2024 Bentham Science Publishers.